PREPARATION AND EVALUATION OF SOLID DISPERSIONS OF ACECLOFENAC (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Aceclofenac is a potent anti-inflammatory analgesic agent indicated for acute and chronic treatment of rheumatoid arthritis, ostio arthritis, and onkylosing spondylytis. Aceclofenac is poorly water soluble and may show dissolution limited absorption. Solid dispersions (SDs) of Aceclofenac in PEG-6000, PVP were prepared by solvent evaporation method. The solid dispersion was characterized for physical appearance, solubility and IR. FTIR study reveled that drug was stable in SDs. Solubility of Aceclofenac from SDs increased in distilled water. The drug content was found to be high and uniformly distributed in the all formulation. Dissolution of drug increased from all the solid dispersion. Dissolution of Aceclofenac increased with increase in the proportion of carriers (1:1, 1:5, and 1:9). Of both the carriers used, dissolution of the drug was more in PEG 6000 based SDs. It is concluded that dissolution of the Aceclofenac could be improved by solid dispersion and PEG 6000 based solid dispersions were more effective in the enhancing the dissolution.